2013
DOI: 10.2147/ijwh.s33125
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of different dosage of mifepristone for the treatment of uterine fibroids: a double-blind randomized clinical trial

Abstract: ObjectivesThe aim of this study was to evaluate the safety and improvement in quality of life using 10 mg and 5 mg daily doses of mifepristone for the treatment of uterine fibroids.DesignThe research was a randomized double-blind clinical study undertaken at the Eusebio Hernández Hospital in Havana, Cuba.Subjects and methodsSeventy subjects with symptomatic uterine fibroids took one daily capsule of 10 mg or 5 mg mifepristone orally for 9 months. One to three endometrial biopsies were performed. In evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
(27 reference statements)
1
15
0
3
Order By: Relevance
“…Current studies support that growth of myoma is dependent on progesterone and therefore antiprogestins (mifepristone) and selective progesterone receptor modulators (SPRMs-Asoprisnil/Ulipristal) can be effective in treatment. Several clinical trials have been done since then with doses varying from 2.5 to 100 mg for 3-12 months [4]. Studies have found that a dose of 2.5 mg is not effective in reducing the myoma volume, but a dose as low as 5 mg per day and maximum as high as 50 mg per day was found effective [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies support that growth of myoma is dependent on progesterone and therefore antiprogestins (mifepristone) and selective progesterone receptor modulators (SPRMs-Asoprisnil/Ulipristal) can be effective in treatment. Several clinical trials have been done since then with doses varying from 2.5 to 100 mg for 3-12 months [4]. Studies have found that a dose of 2.5 mg is not effective in reducing the myoma volume, but a dose as low as 5 mg per day and maximum as high as 50 mg per day was found effective [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have been done since then with doses varying from 2.5 to 100 mg for 3-12 months [4]. Studies have found that a dose of 2.5 mg is not effective in reducing the myoma volume, but a dose as low as 5 mg per day and maximum as high as 50 mg per day was found effective [4,5]. In the present observational prospective ''before-after'' study, 50 mg mifepristone given once a week was used for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest, almost pure antiprogestin, mifepristone, has shown great effectiveness with different dosages in multiple studies into the treatment of this condition [5, 6]. Mifepristone in 5 mg doses has proven itself to be an efficient and safe therapeutic medicine as well as achieving an observable improvement in quality of life [510]. Eisinger et al in a 17-case pilot study using 2.5 mg doses of mifepristone obtain lesser reductions in uterine volume, but a similar quality of life in comparison with 5 mg mifepristone [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in follow-up biopsies taken 6 months after the end of the treatment, these changes were shown to be reversible and comparable to control groups and to baseline occurrence. For mifepristone, after 9 months exposure a comparable frequency of PAEC could be observed [69].…”
Section: Tolerability Profile Of Sprmsmentioning
confidence: 74%
“…For mifepristone, after 3 months of therapy, a thickening of the endometrium of >8 mm was observed for 21.2 and 48.6% of subjects in the 5 and 10 mg group, respectively. The frequency of occurrence did not increase with prolonged treatment exposure up to 9 months (TABLE 1) [69].…”
Section: Tolerability Profile Of Sprmsmentioning
confidence: 91%